Preparation of cattle bone collagen peptides-calcium chelate and its structural characterization and stability. (June 2021) - Zhang, Hongru; Zhao, Laiyu; Shen, Qingshan; Qi, Liwei; Jiang, Shan; Guo, Yujie; Zhang, Chunhui; Richel, Aurore
Abstract: In this study, cattle bone collagen peptides (CPs) were applied to prepare peptides-calcium chelate (CPs-Ca), and the physicochemical, structural properties, and stability of the CPs-Ca were characterized. The optimized preparation conditions were determined by single factor test, and the maximum calcium-chelating capacity was 42.70 ± 1.09 μg/mg. Physicochemical analysis indicated that CPs-Ca was a new substance compared with CPs. Structural analysis demonstrated that calcium ions chelated CPs via the sites of carboxyl oxygen, hydroxyl oxygen and amino nitrogen atom. Morphology analysis showed that CPs-Ca aggregated to large particles due to the crosslinking of calcium ions. According to the stability analysis, CPs-Ca was stable in thermal processing and gastrointestinal digestion. The acid environment was the major factor of CPs-Ca dissociation. The findings put forward a scientific basis for preparing a novel calcium supplement and high-value utilization of cattle bone. Highlights: The cattle bone collagen peptides-calcium chelate was prepared. The process conditions were optimized and calcium-binding capacity was 42.70 μg/mg. The chelate was different from peptides in physicochemical property, and structure. Chelate was stable in intestinal digestion under action of protease and weak base. Gastric digestion was the main place where chelate released calcium due to H + .